Game theory and applications : 3rd Joint China-Dutch Workshop and 7th China Meeting, GTA 2016, Fuzhou, China, November 20-23, 2016, Revised selected papers /: 3rd Joint China-Dutch Workshop and 7th China Meeting, GTA 2016, Fuzhou, China, November 20-23, 2016, Revised selected papers. (2017) - Unknown
No abstract available